2018
DOI: 10.1186/s12886-018-0877-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing amblyopia treatment using multifocal visual evoked potentials

Abstract: BackgroundTo evaluate the effect of occlusion treatment for anisometropic amblyopia using multifocal visual evoked potentials (mfVEPs).MethodsThe patients for this study comprised 19 patients (mean age 6.05 ± 1.65 years) with anisometropic amblyopia underwent mfVEP analysis using the RETIscan® system before and after occlusion treatment. After dividing the area into six ring areas and four quadrants, we analyzed the amplitudes and latencies of the mfVEPs.ResultsThe amplitudes of ring 1 (central field) in ambly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…The latency of the P100 wave in amblyopia eyes is longer and the amplitude is lower than in normal eyes. Visual evoked potentials have been widely used as a diagnostic and therapeutic evaluation of amblyopia [32, 33]. In our experiment, the latency of the P100 wave in amblyopic eyes of amblyopic kittens was longer and the amplitude was lower than those in the contralateral eyes and the ipsilateral eyes of the control group, consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…The latency of the P100 wave in amblyopia eyes is longer and the amplitude is lower than in normal eyes. Visual evoked potentials have been widely used as a diagnostic and therapeutic evaluation of amblyopia [32, 33]. In our experiment, the latency of the P100 wave in amblyopic eyes of amblyopic kittens was longer and the amplitude was lower than those in the contralateral eyes and the ipsilateral eyes of the control group, consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…The latency of the P100 wave in amblyopia eyes is longer and the amplitude is lower than in normal eyes. Visual evoked potentials have been widely used as a diagnostic and therapeutic evaluation of amblyopia [31,32]. In our experiment, the latency of the P100 wave in amblyopic eyes of amblyopic kittens was longer and the amplitude was lower than those in the contralateral eyes and the ipsilateral eyes of the control group, consistent with the results of previous studies.…”
Section: Vip Immunohistochemistrysupporting
confidence: 92%
“…20 After 3 weeks of monocular deprivation, the latency of P100 in the deprived eyes was longer than that in the control group, and the amplitude decreased, which was the same as the application of PVEP in amblyopia. 21,22 Due to amblyopia, many neurons in the lateral geniculate body could not receive effective signal stimulation. Immunohistochemistry and Western blotting showed that BDNF was expressed in the cytoplasm of neurons, and the expression of BDNF in the lateral geniculate body of amblyopic cats was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 99%